The role of Financial Technology (Fintech) in Improving Financial Literacy and Inclusion in Indonesia - Christiaan, Pemy; Rosalia, Olyvia; Firayani, Firayani; Noviya, Anis (Maneggio, 2025)
This study aims to analyze the role of Financial Technology (Fintech) in improving financial literacy and inclusion in Indonesia. Fintech has grown rapidly and become a solution for people who previously had limited access to formal financial services. Using quantitative methods, this study involved 310 respondents who are users of Fintech services in Indonesia. Data was collected through an online questionnaire and analyzed using multiple linear regression and Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results showed that the use of Fintech has a significant effect on improving financial literacy, especially through the financial education feature in the application. In addition, Fintech also plays a role in increasing financial inclusion by providing wider access to digital banking services, online loans, and digital-based investments. However, there are some challenges in utilizing Fintech, such as low digital literacy and concerns regarding data security. Therefore, policies that support the development of Fintech that are more inclusive and educative are needed so that the benefits can be optimally felt by the community.